Mid-Miocene thermal impact on the lithosphere by sub-lithospheric convective mantle material: Transition from high- to moderate-Mg magmatism beneath Vitim Plateau, Siberia - Irina Chuvashova (Geoscience Frontiers, 2017)
High-Mg lavas are characteristic of the mid-Miocene volcanism in Inner Asia. In the Vitim Plateau, small volume high-Mg volcanics erupted at 16–14 Ma, and were followed with voluminous moderate-Mg lavas at 14–13 Ma. In the former unit, we have recorded a sequence of (1) initial basaltic melts, contaminated by crustal material, (2) uncontaminated high-Mg basanites and basalts of transitional (K–Na–K) compositions, and (3) picrobasalts and basalts of K series; in the latter unit a sequence of (1) initial basalts and basaltic andesites of transitional (Na–K–Na) compositions and (2) basalts and trachybasalts of K–Na series. From pressure estimation, we infer that the high-Mg melts were derived from the sub-lithospheric mantle as deep as 150 km, unlike the moderate-Mg melts that were produced at the shallow mantle. The 14–13 Ma rock sequence shows that initial melts equilibrated in a garnet-free mantle source with subsequently reduced degree of melting garnet-bearing material. No melting of relatively depleted lithospheric material, evidenced by mantle xenoliths, was involved in melting, however. We suggest that the studied transition from high- to moderate-Mg magmatism was due to the mid-Miocene thermal impact on the lithosphere by hot sub-lithospheric mantle material from the Transbaikalian low-velocity (melting) domain that had a potential temperature as high as 1510 °С. This thermal impact triggered rifting in the lithosphere of the Baikal Rift Zone.